2023
DOI: 10.3390/molecules28052351
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Quantum Dots-Based Fluorescent Sensor for Determination of the Anticancer Dacomitinib: Application to Dosage Forms

Abstract: One of the most promising drugs recently approved for the treatment of various types of cancer is dacomitinib, which belongs to the tyrosine kinase inhibitor class. The US Food and Drugs Administration (FDA) has recently approved dacomitinib as a first-line treatment for patients suffering from non-small cell lung cancer (NSCLC) with epidermal growth factor receptor (EGFR) mutations. The current study proposes the design of a novel spectrofluorimetric method for determining dacomitinib based on newly synthesiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…As these values exceeded the maximum diffusion rate constant (2.0 × 10 10 L mol −1 s −1 ) by a signicant amount, 43 as a result, it was concluded that, static quenching mechanism was found to be responsible for the NSC-dots uorescence intensity quenching in presence of the studied drug. 43,44 For further investigation of the possible quenching mechanism between the synthesized NSC-dots and NFX the inner lter effect was studied. The inner lter effect, previously thought to be an analytical error, has recently begun to establish itself in the eld of analysis as a substantial quenching mechanism involving an energy conversion unrelated to radiation.…”
Section: Resultsmentioning
confidence: 85%
See 2 more Smart Citations
“…As these values exceeded the maximum diffusion rate constant (2.0 × 10 10 L mol −1 s −1 ) by a signicant amount, 43 as a result, it was concluded that, static quenching mechanism was found to be responsible for the NSC-dots uorescence intensity quenching in presence of the studied drug. 43,44 For further investigation of the possible quenching mechanism between the synthesized NSC-dots and NFX the inner lter effect was studied. The inner lter effect, previously thought to be an analytical error, has recently begun to establish itself in the eld of analysis as a substantial quenching mechanism involving an energy conversion unrelated to radiation.…”
Section: Resultsmentioning
confidence: 85%
“…The quenching mechanism can generally be divided into a variety of categories, including dynamic quenching, static quenching, and the inner lter effect (IFE). 43,44 Fluorophore and quencher molecular interaction may cause static or dynamic quenching. The quencher in dynamic quenching diffuses to the uorophore at the excited state.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As a result, they are ideal candidates for sensing applications . Also, CQDs can determine non-fluorescent drugs by fluorescence quenching, which is a great advantage for sensing drugs . CQDs have been utilized in numerous fields, such as nanosensing, bioimaging, catalysis, and optoelectronic uses.…”
Section: Introductionmentioning
confidence: 99%
“…The introduction of heteroatoms, such as boron (B), sulfur (S), nitrogen (N), and phosphorous (P) into the overall structure-of-CQDs, with or without surface changes, is known as doping. Doping CQDs increases their quantum yields and improves their fluorescence qualities, allowing them to be used in various applications [45][46][47][48][49][50][51] . Because nitrogen has an atomic radius similar to that of carbon, and sulfur and carbon have similar electronegativity, SN-CQDs represent one of the most important doped-CQDs 52 .…”
mentioning
confidence: 99%